The Concept of Miracle in Hume's Philosophy - Sezgül, İbrahim (Journal of History Culture and Art Research, 2013)
The aim of this article is to provide an overview of the definition of miracle and then to dwell on Hume’s views on the term miracle. Controversy over the conception of miracle focuses primarily on whether a miracle must be, in some sense, contrary to natural law or be a violation of natural law. Hume’s first argument regarding miracle attempts to show the impossibility of miracles and his second argues against the ability to know whether a miracle has ever occurred. Dwelling on the various definitions of miracle, this article will elaborate on Hume’s ideas on miracle and criticisms leveled against them.